The UTM students' perspective on cooperative learning - Gunasagaran, Kavitha (2006)
The purpose of this study is to look at the studentsâ€™ perspective on cooperative learning at Universiti Teknologi Malaysia in Johor Bharu, Johor. This study is also to determine if there is any significant difference between male and female students and between the studentsâ€™ perspective for eight faculties on cooperative learning. The studentsâ€™ perspective on cooperative learning questionnaire was used as the research instrument to look at the studentsâ€™ perspective on cooperative learning. A sample of 291 students which was chosen randomly from first to fifth year was involved in the research. The studentsâ€™ perspective on cooperative learning was divided into six categories, which are Attitude Related to Teamwork, Collaboration, Communication Skills, Understanding the Course, Interpersonal Skills and Problem Solving Skills. Data collected were analyzed by using SPSS software version 11.5. t-test was used to determine if there is any significant difference between male and female studentsâ€™ perspective on cooperative learning while one way ANOVA wad used to determine if there is any significant difference between the studentsâ€™ perspective for eight faculties on cooperative learning. Result shows that, the studentsâ€™ perspective on cooperative learning are positive. Most of the students chose â€œagreeâ€? response for the statements in the questionnaire. There are a significant difference between the male and female studentsâ€™ perspective on cooperative learning but not for the studentsâ€™ perspective for the eight faculties. Several recommendations were made at the end of the report for further research.